FORMATION OF THE SYSTEM OF FINANCIAL SUPPORT OF INSTITUTIONS OF GENERAL SECONDARY EDUCATION - Шлапак, Алла В.; Жукова, Юлія М. (Journal of Strategic Economic Research, 2023)
The main components of the process of formation of the system of financial support of institutions of general secondary education are determined in the presented work. The main characteristics of the financing system of educational institutions are presented, and the main opportunities and threats of the presented process are identified. The purpose of the presented work is to study the process of forming a system of financial support for institutions of general secondary education. The formation of the system of financial support of institutions of general secondary education is an important task that affects the quality of the provision of educational services and the development of the educational process. The main aspects of the formation of such a system are: budgeting, financial plan, attraction of additional funds, effective use of funds, financial reporting, investment, state support. One of the main tools of financial support of educational institutions is budgeting. It determines the amount of financing, sources of funds, as well as the distribution of these funds for various needs of the institution. To ensure the development of general secondary education institutions, it is necessary to attract additional funds, for example, through sponsorship, donations from parents and public organizations. Rational and effective use of financial resources is an important aspect of the formation of the financial support system. This involves cost control and cost optimization. State support in the form of subventions, grants and other programs can significantly contribute to the financial support of general secondary education institutions. It should also be noted that institutions of general secondary education can attract investments for the implementation of development projects and modernization of the educational process. The formation of a financial support system requires purposeful work, strategy development and constant monitoring of the implementation of financial plans. The starting point should be the needs and interests of general secondary education institutions, their development plans, and a mission focused on quality education and the creation of favorable conditions for the development of students.